Manajemen Program Satu Keluarga Satu Sarjana Kota Pariaman - Nurmaitasari; Putera, Roni Ekha; Ria Ariyani (Jurnal Administrasi Publik dan Pemerintahan, 2024)
This article explains the management of the One Family One Scholar Program in the city of Pariaman. The background of this research is based on the observation that the college participation rate in Indonesia is still very low, and the average length of schooling is also low. As a result, several educational programs have been created by the government, including the Pariaman City Government's One Family One Scholar Program. This program has been established since 2018 with the aim of eradicating poverty and improving the quality of human resources. The research was analyzed using a qualitative method with the management function theory by Ricky W. Griffin, which consists of planning, organizing, directing, and controlling. The results of the research indicate that the management of the One Family One Scholar Program in Pariaman has been running well, and all stages of management, including planning, organizing, directing, and controlling, have been carried out. However, there are still some challenges in its implementation, such as the absence of specific planning made since the beginning to address all obstacles. The city government only relies on the initial planning of this program, even though it is no longer effective. For example, the target set by the Pariaman City Government has never been achieved in the past 5 years, despite several evaluations and improvements made to the program